Geological Heterogeneity of Coastal Unconsolidated Groundwater Systems Worldwide and Its Influence on Offshore Fresh Groundwater Occurrence - Zamrsky, Daniel; Karssenberg, Maria E.; Cohen, Kim M.; Bierkens, Marc F. P.; Oude Essink, Gualbert H. P. (Frontiers in Earth Science, 2020)
Numerous coastal areas worldwide already experience fresh water shortages due to overexploitation and salt water intrusion. Future climate change and population growth will further intensify this threat in more areas in coming decades. Therefore, it is necessary to explore any potential fresh water source, such as offshore fresh groundwater, that could alleviate this fresh water shortage and provide valuable time for adaptation measures implementation and changes in water management strategies. Recent evidence suggests that a disproportionally large portion of human population living in coastal areas relies on groundwater resources stored in underlying unconsolidated groundwater systems. These systems are often very heterogeneous, combining numerous high permeability aquifers interlaid with low permeability aquitards with varying total thickness. This heterogeneity is a major control on the fresh groundwater volume and groundwater salinity distribution within such systems. Thus, the quantification of geological heterogeneity is often the limiting factor when estimating fresh groundwater volumes, both inland and offshore, along the global coastline. To overcome this obstacle, we combine conceptual geological models with available state-of-the-art global datasets to derive a set of geological heterogeneity parameter distributions quantifying geological heterogeneity of coastal unconsolidated groundwater systems as formed over last 1 Ma. These are then used in an algorithm designed to build synthetic heterogenic parameterizations of coastal unconsolidated groundwater systems along the global coastline. These, in turn, provide key input for modelling variable-density groundwater flow and coupled salt transport to analyze changes in groundwater salinities and offshore fresh groundwater volume. Such an analysis is performed over one full glacial-interglacial cycle (the last 0.13 Ma) to account for oscillating sea-level conditions and shifts in coast-line positions and salinity incursions. Our simulation results show a close match between the modelling scenarios and values presented by literature sources demonstrating the potential of the hereby presented methodology to be applied in similar future studies.